Rapid improvement of guttate psoriasis following inadequate response to prior systemic therapy using 311 nm narrowband ultraviolet B (NB-UVB) phototherapy - Rizka Fauziyah; Hardyanto Soebono; Arief Budiyanto (Indonesian Journal of Biomedicine and Clinical Sciences, 2026)
Guttate psoriasis (GP) is a variant of psoriasis commonly affecting children and young adults, often triggered by infection. Although most cases respond to topical therapy, some patients show inadequate response to prior treatment. Narrowband ultraviolet B (NB-UVB) phototherapy is considered a safe and effective therapeutic option in such cases. A 12-year-old boy presented with multiple erythematous papules with fine scales distributed over the trunk and extremities. Laboratory findings revealed elevated antistreptolysin-O titers. Based on the clinical and histopathology features, the patient was diagnosed with GP. The patient had previously received low-dose methotrexate therapy (2.5 mg/week) for approximately six months with inadequate clinical response. NB-UVB phototherapy was initiated three times weekly with gradual dose escalation. Marked clinical improvement was observed after 18 sessions, achieving PASI90. NB-UVB phototherapy exerts therapeutic effects through immunomodulation and reduction of keratinocyte proliferation. The rapid response observed in this case may be related to lesion characteristics and the appropriate selection of therapy following subtherapeutic methotrexate dosing. Based on this case, it can be concluded that NB-UVB phototherapy may be an effective and well-tolerated treatment option for GP with inadequate response to prior therapy, particularly in pediatric patients.